PENGEMBANGAN MEDIA PEMBELAJARAN PRAKTIKUM BERBASISS VIDEO ANIMASI PADA MATERI SISTEM PENCERNAAN DI KELAS XI SMA NEGERI 21 MAKASSAR - Haslipa M; Andi Asmawati Aziz; Muhammad Khalifah Mustami (UNM Journal of Biological Education, 2021)
This study aims to produce an animated video-based practicum learning media on the digestive system material in class XI SMA Negeri 21 Makassar that is valid, practical and effective. The type of this study is research and development (R&D) by adapting the 4-D development model which of the stages of definition (Define), design (Design), development (Development), and dissemination (Disseminate). Data collection uses expert validation sheets to collect media validity data, teacher and student response questionnaires to examine the practicality of the media and learning outcomes tests to see the effectiveness of the media. This study was conducted from November to June 2021 at SMA Negeri 21 Makassar. The results showed that the animation video-based practicum learning media on the digestive system material in class XI SMA has met the criteria for good media. In addition, the developed media has met the validity criteria with a validity value of 87.6%, the category is very valid. Meet the practicality criteria with the teacher's response value is 79% in the practical category and the student response is 76.86% in the practical category. Meet the effective criteria with an average value of 96,87% of students in the effective category. Therefore, the conclusion of the study is the animated video-based practicum learning media developed meets the criteria of validity, practicality and effectiveness.